2011
DOI: 10.4061/2011/120925
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tumor Associated Fibroblasts in Human Liver Regeneration, Cirrhosis, and Cancer

Abstract: Tumor associated fibroblasts (TAFs) are considered a microenvironmental element critical for tumor growth and progression. Experimental studies suggest that their origin could be from mesenchymal stem cells (MSCs) derived from the bone marrow. However, the role played by TAFs in cirrhosis, hepatocellular carcinoma development, and progression is largely unknown, and in vitro human models are missing. This paper for the first time demonstrates that (1) human neoplastic livers possess a population of multipotent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…The origin of the myofibroblasts and CAFs might be derived from the epithelial mesenchymal transition (EMT), resident fibroblasts, or bone marrow derived stem cells. It has been demonstrated that multipotent adult stem cells with CAFs properties was found not only in HCC, but also in cirrhotic liver, supporting the evidence that the CAFs could be originated from resident progenitor cells [27]. …”
Section: Discussionmentioning
confidence: 81%
“…The origin of the myofibroblasts and CAFs might be derived from the epithelial mesenchymal transition (EMT), resident fibroblasts, or bone marrow derived stem cells. It has been demonstrated that multipotent adult stem cells with CAFs properties was found not only in HCC, but also in cirrhotic liver, supporting the evidence that the CAFs could be originated from resident progenitor cells [27]. …”
Section: Discussionmentioning
confidence: 81%
“…Cells from glioma were isolated and cultured applying, with minor modifications, previously described protocols . Briefly, glioma fragments were mechanically enzymatically dissociated and cells less than 40 ”m in diameter were cultured in expansion medium as in . See Supporting Information methods for details.…”
Section: Methodsmentioning
confidence: 99%
“…After enzymatic detachment, cells were incubated with properly conjugated or unconjugated antibodies. The analysis was performed either by FACS‐Calibur, FACScanto (BD Biosciences, San Jose, CA, http://www.bdbiosciences.com), or by CyAn (Beckman Coulter s.r.l., Milan, Italy, https://www.beckmancoulter.com) . Exosome staining was performed after incubation of exosomes with 4 ”m aldehyde/sulfate latex beads (Molecular Probes, Invitrogen, Carlsbad CA, http://www.lifetechnologies.com).…”
Section: Methodsmentioning
confidence: 99%
“…This was demonstrated after implantation of integrin α11-deficient fibroblasts and NSCLC cells in SCID mice caused reduction of tumor volume, which was restored upon re-expression of α11 in knock-out mouse embryonic fibroblasts. Similarly, a population of CAFs from hepatocellular carcinoma liver tissue demonstrated significantly higher surface expression of integrin α4 and lower expression of α2 when compared to nonneoplastic tissue [165]. CAFs express several alpha subunits, including αV and α5, which interact with multiple beta subunits, and are capable of binding collagen, fibronectin, and soluble factors such as TGF-ÎČ1 [166–168].…”
Section: Transmembrane Proteinsmentioning
confidence: 99%